Positive electrode lithium supplementing agent, preparation method and application thereof

CN114530634BActive Publication Date: 2026-10-27HUAWEI TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202011332764.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-23
Publication Date
2026-10-27
Estimated Expiration
2040-11-23

AI Technical Summary

Technical Problem

目前正极补锂剂的选择种类较少,通常为Li2NiO2、Li6CoO4等富锂材料,且这些正极补锂剂在脱锂后留在正极侧的残留物会增加电芯阻抗、催化电解液产气等

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114530634B_ABST
    Figure CN114530634B_ABST
Patent Text Reader

Abstract

The embodiment of the present application provides a positive electrode lithium supplementing agent, which comprises a catalyst and a lithium-rich material; the catalyst is an oxide type positive electrode active material, and the intensity ratio of the diffraction peak of the (003) crystal face to the diffraction peak of the (104) crystal face of the catalyst is less than or equal to 2; the catalyst is used for catalyzing the decomposition of the lithium-rich material to release active lithium; and the lithium-rich material comprises at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate and lithium acetate. In the presence of the catalyst, the positive electrode lithium supplementing agent can release active lithium ions at a lower voltage, and the residue after lithium extraction will not increase the risk of gas production of the battery electrolyte, will not increase the impedance of the battery cell, and can achieve a better lithium supplementing effect. The embodiment of the present application also provides a preparation method of the positive electrode lithium supplementing agent, a battery positive electrode sheet, an electrochemical battery and a terminal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a positive electrode lithium replenishing agent for battery positive electrode, its preparation method and application. Background Technology

[0002] With economic and technological development, industries such as portable electronic devices (mobile phones, tablets, laptops, etc.), drones, and electric vehicles urgently need energy storage devices with higher energy density and longer cycle life. To enable lithium-ion batteries to meet these requirements, the industry typically adds lithium replenishing agents that provide active lithium to the lithium-ion battery system in advance to compensate for the irreversible loss of active lithium during battery manufacturing and cycling.

[0003] Currently, lithium replenishment methods in batteries can be mainly divided into positive electrode lithium replenishment and negative electrode lithium replenishment. Positive electrode lithium replenishment involves adding a positive electrode lithium replenishing agent to the positive electrode system. Currently, the selection of positive electrode lithium replenishing agents is limited, typically consisting of lithium-rich materials such as Li2NiO2 and Li6CoO4. Furthermore, the residues left on the positive electrode side after delithiation of these agents can increase cell impedance and catalyze electrolyte gas production. Summary of the Invention

[0004] In view of this, this application provides a positive electrode lithium replenishment agent, which uses an oxide-type positive electrode active material with an intensity ratio of (003) to (104) crystal plane diffraction peaks ≤2 as a catalyst. It can catalyze the release of active lithium from lithium-rich materials at a lower voltage. Moreover, the residue left on the positive electrode side after the positive electrode lithium replenishment agent is delithiated will not increase the risk of electrolyte gas generation or cell impedance, thus broadening the selection range of positive electrode lithium replenishment agents.

[0005] Specifically, the first aspect of this application provides a positive electrode lithium replenishment agent, which includes a catalyst and a lithium-rich material; the catalyst is an oxide-type positive electrode active material, and the intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak of the catalyst is less than or equal to 2; the catalyst is used to catalyze the decomposition of the lithium-rich material to release active lithium; the lithium-rich material includes at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate.

[0006] The cathode lithium replenishment agent provided in this application includes a lithium-rich material and a catalyst. The catalyst is an oxide-type cathode active material with special XRD properties, exhibiting good catalytic activity. It can catalyze the decomposition of the originally high-delithiation-potential lithium-rich material at a lower potential during the battery formation stage, releasing active lithium ions. This enriches the selection range of cathode lithium replenishment agents. The cathode lithium replenishment agent has a high lithium replenishment capacity, effectively compensating for the irreversible consumption of active lithium by the battery, thus improving battery performance. Furthermore, the cathode lithium replenishment agent leaves less residue on the cathode side after delithiation and does not increase the risk of electrolyte gas generation, cell impedance, or reduce battery energy density.

[0007] In some embodiments of this application, the intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak of the catalyst is 1.0-1.8. In this case, the catalyst has higher catalytic activity.

[0008] In this application embodiment, the oxide-type positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt aluminum oxide.

[0009] In some embodiments of this application, the oxide-type cathode active material further contains doping elements, including at least one selected from B, P, N, Mg, Al, Ca, Ba, La, Zr, Mo, Nb, Ti, V, Sn, Sb, Cr, Fe, Cu, and Zn. Suitable doping elements can alter the intrinsic electron orbital overlap, surface properties, and improve structural stability of the oxide-type cathode active material.

[0010] In this embodiment, the catalyst has a particle size of 10 nm to 25 μm. The particle size of the catalyst can be selected according to the electrochemical activity of the lithium-rich material. For example, when the electrochemical activity of the lithium-rich material is low, using a catalyst with a smaller particle size is more conducive to its decomposition.

[0011] In this embodiment, the surface of the catalyst is coated with the lithium-rich material, and / or the catalyst is dispersed in the lithium-rich material. This allows the catalytic activity of the catalyst to be maximized.

[0012] In this embodiment, the mass ratio of the lithium-rich material to the catalyst is 1:(0.01-100). Controlling the mass ratio of the lithium-rich material to the catalyst can regulate the initial delithiation capacity of the cathode lithium replenishment agent.

[0013] In some embodiments of this application, the lithium-rich material forms a lithium-rich material coating layer with a thickness of 10 nm-20 μm on the surface of the catalyst. When the catalyst and the lithium-rich material are coated, the catalytic activity of the catalyst can be maximized.

[0014] In some embodiments of this application, the positive electrode lithium supplement agent further includes a protective layer encapsulating the catalyst and the lithium-rich material, the protective layer having ionic conductivity. The protective layer can further improve the stability and processing performance of the positive electrode lithium supplement agent, especially when the lithium-rich material is lithium oxide or lithium peroxide.

[0015] In this embodiment, the protective layer is made of at least one of lithium fluoride, lithium carbonate, lithium oxalate, lithium acetate, lithium phosphate, inorganic conductive carbon, organic polymers, and inert oxides. These protective layers do not increase the risk of gas generation in the battery electrolyte.

[0016] In this embodiment, the thickness of the protective layer is 5nm-200nm. A suitable protective layer thickness can ensure that the positive electrode lithium replenishment agent has good processing performance, while avoiding excessive thickness from affecting the timely release of active lithium and increasing battery impedance.

[0017] In this embodiment, the mass of the protective layer is 0.01%-10% of the mass of the positive electrode lithium supplement. A lower proportion of the protective layer mass ensures that the positive electrode lithium supplement has good processing performance without excessively increasing the residual mass of the positive electrode lithium supplement after delithiation.

[0018] In this embodiment of the application, the particle size of the positive electrode lithium replenishing agent is 50nm-30μm.

[0019] The second aspect of this application also provides a method for preparing a positive electrode lithium supplement, including:

[0020] The oxide-type positive electrode active material is restructured to obtain a catalyst; then the catalyst is physically fused with a lithium-rich material to obtain a positive electrode lithium supplement agent.

[0021] Alternatively, an oxide-type positive electrode active material can be mixed with a lithium-rich material and then subjected to high-energy ball milling to obtain a positive electrode lithium replenishing agent; the positive electrode lithium replenishing agent includes a catalyst and the lithium-rich material, wherein the catalyst is an oxide-type positive electrode active material with lattice reconstruction;

[0022] Wherein, the intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak of the catalyst is less than or equal to 2, the catalyst is used to catalyze the decomposition of the lithium-rich material to release active lithium, and the lithium-rich material includes at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate and lithium acetate.

[0023] In some embodiments of this application, the lattice reconstruction method includes one of the following: a) high-energy ball milling of the oxide-type positive electrode active material; b) high-energy ball milling of the oxide-type positive electrode active material with a compound of a Group 3 and / or Group 5 element followed by sintering.

[0024] In some embodiments of this application, the rotational speed of the high-energy ball mill is greater than or equal to 350 r / min.

[0025] In some embodiments of this application, the physical fusion is a low-speed ball milling with a rotation speed of less than or equal to 300 r / min.

[0026] In some embodiments of this application, the preparation method further includes: constructing a protective layer encapsulating the catalyst and the lithium-rich material. This is particularly relevant when the lithium-rich material contains at least one of lithium oxide and lithium peroxide. In one specific embodiment, the protective layer is constructed by subjecting the core material obtained by physically fusing the catalyst and the lithium-rich material to heat treatment in dry air or a carbon dioxide atmosphere. This allows for the in-situ formation of a dense lithium carbonate protective layer.

[0027] The method for preparing the positive electrode lithium replenishing agent provided in the second aspect of the embodiments of this application is simple, efficient and environmentally friendly, and can be mass-produced.

[0028] A third aspect of this application also provides a battery positive electrode sheet, the battery positive electrode sheet including a current collector and a positive electrode material layer disposed on the current collector, the positive electrode material layer including a positive electrode lithium supplement, a positive electrode active material, a binder and a conductive agent as described in the first aspect of this application.

[0029] During the fabrication of the positive electrode sheet of this battery, the viscosity of the positive electrode slurry used to form the aforementioned positive electrode material layer is adjustable, preventing gelation and facilitating the coating to obtain a film layer with high smoothness. Electrode sheets containing this positive electrode lithium supplement can be used to provide electrochemical batteries with high energy density and long cycle life.

[0030] A fourth aspect of this application also provides an electrochemical battery, including a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the positive electrode is the positive electrode sheet of the battery described in the third aspect of this application. This electrochemical battery has high energy density and long cycle life.

[0031] A fifth aspect of this application also provides a terminal, the terminal including a housing, a motherboard and a battery located inside the housing, the battery including the electrochemical battery described in the fourth aspect of this application, the electrochemical battery being used to power the terminal. This terminal can be an electronic product such as a mobile phone, laptop, tablet computer, portable computer, or smart wearable product. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of the structure of the positive electrode lithium replenishing agent provided in one embodiment of this application;

[0033] Figure 2aThis is a schematic diagram of the structure of the positive electrode lithium replenishing agent provided in one embodiment of this application;

[0034] Figure 2b This is a schematic diagram of the structure of the positive electrode lithium replenishing agent provided in another embodiment of this application;

[0035] Figure 2c This is a schematic diagram of the structure of the positive electrode lithium replenishing agent provided in another embodiment of this application;

[0036] Figure 3 This is a schematic diagram of the structure of the positive electrode sheet of the battery provided in one embodiment of this application;

[0037] Figure 4 This is a schematic diagram of the terminal structure provided in the embodiments of this application;

[0038] Figure 5 The image shows the X-ray diffraction (XRD) pattern of the catalyst in the positive electrode lithium replenishment agent of Example 1 of this application;

[0039] Figure 6 The image shows the XRD pattern of the positive electrode lithium replenishing agent in Example 1 of this application;

[0040] Figure 7 The charge-discharge curves (a) of the positive electrode lithium replenishment agent in Example 1, and the charge-discharge curves (b) of the coin cell battery made by mixing the positive electrode lithium replenishment agent with lithium cobalt oxide. Detailed Implementation

[0041] Lithium-ion batteries mainly consist of a positive electrode, a negative electrode, an electrolyte, and a separator. All the active lithium in a lithium-ion battery is provided by the positive electrode material. However, due to the initial coulombic efficiency mismatch between the positive and negative electrode materials and the formation of a solid electrolyte interphase (SEI) film on the negative electrode surface during the first charge, some of the active lithium in the positive electrode is consumed at the negative electrode, resulting in a loss of cyclic lithium. This affects the specific capacity of the positive electrode material and reduces the battery's energy density. Furthermore, irreversible chemical side reactions during battery cycling and the thickening of the SEI due to volume changes in the negative electrode material also consume a significant amount of active lithium, further impacting battery lifespan. To improve the energy density and cycle performance of lithium-ion batteries, this application provides a positive electrode lithium replenisher with good lithium replenishment effect. The embodiments of this application will be described below with reference to the accompanying drawings.

[0042] Please see Figure 1This application provides a positive electrode lithium replenisher 100 for use in the positive electrode of a battery. The positive electrode lithium replenisher 100 includes a catalyst 1 and a lithium-rich material 12. The catalyst 11 is made of an oxide-type positive electrode active material. The intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak of the catalyst 11 is less than or equal to 2. The catalyst 11 is used to catalyze the decomposition of the lithium-rich material 12 to release active lithium. The lithium-rich material 12 includes at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate.

[0043] In this embodiment of the application, the lithium-rich material 12 can be coated on the surface of the catalyst 11 (see [reference]). Figure 1 The catalyst 11 is dispersed in the lithium-rich material 12 (not shown in the figure), and / or the catalyst 11 is dispersed in the lithium-rich material 12. This allows the catalytic activity of the catalyst 11 to be maximized. Furthermore, the lithium-rich material 12 can be as follows: Figure 1 The catalyst 11 can be coated on its entire surface as in the example, or only a portion of its surface can be coated.

[0044] The catalyst 11 in the positive electrode lithium replenishment agent can be referred to as "the oxide-type positive electrode active material after lattice reconstruction". Compared with ordinary oxide-type positive electrode active materials, the intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak of the catalyst 11 obtained after lattice reconstruction is smaller, some crystal planes are exposed, the surface is rougher, and it exhibits catalytic activity. In addition, the lithium intercalation capacity of the oxide-type positive electrode active material after lattice reconstruction is lower, and the reversible capacity is smaller, making it more suitable for lithium replenishment. In this application, the catalyst 11 can reduce the delithiation potential of the lithium-rich material 12, which originally has a high delithiation potential (i.e., low electrochemical activity), so that it can delithiate lithium ions within the working voltage range of the lithium-ion battery, thereby achieving the effect of lithium replenishment and enriching the selection range of lithium replenishment agents. Among them, the term "delithiation potential" in this application refers to the lowest voltage at which lithium atoms in the material can be delithiated into the electrolyte to become active lithium ions.

[0045] Furthermore, the residues remaining on the positive electrode side after delithiation of the positive electrode lithium replenisher do not increase the risk of electrolyte gas generation or the cell impedance. Specifically, after delithiation during the battery formation stage, the catalyst 11 of the positive electrode lithium replenisher 100 remains on the positive electrode. Since the catalyst 11 is an oxide-type positive electrode active material, it does not increase the risk of electrolyte gas generation and does not introduce additional substances into the battery cell, thus having little impact on the cell impedance. The gaseous delithiation products of certain lithium-rich materials (such as lithium oxide, lithium peroxide, lithium carbonate, lithium oxalate, etc.) can be discharged during the battery manufacturing process, without occupying the cell's volume and mass, and naturally do not increase electrolyte gas generation. Similarly, the delithiation products of other lithium-rich materials (such as lithium fluoride, lithium acetate) do not increase the risk of electrolyte gas generation and can participate in the formation of the SEI film on the negative electrode, without increasing the cell impedance. Therefore, the aforementioned positive electrode lithium replenisher can achieve a good lithium replenishment effect and can significantly improve the battery's cycle performance and energy density.

[0046] The lithium-rich materials 12 in this application typically have a delithiation potential above 4.5V without a catalyst, which is outside the normal operating voltage range of the battery and is generally not used for lithium replenishment. However, under the action of the catalyst 11 in this application, these lithium-rich materials 12 can release active lithium at a normal battery operating voltage below 4.2V. The delithiation potentials and theoretical specific capacities of the aforementioned lithium-rich materials 12 without a catalyst are shown in Table 1 below.

[0047] Table 1. Delithiation potential and theoretical specific capacity of each lithium-rich material without catalyst.

[0048] Lithium oxide 4.8 1794 Lithium peroxide 4.5 1168 lithium fluoride 5.7 1033 lithium carbonate 4.7 725 lithium oxalate 4.7 526 Lithium acetate 4.8 406

[0049] As shown in Table 1, the lithium-rich materials 12 in this application exhibit high theoretical charge specific capacity (i.e., delithiation capacity), exceeding 400 mAh / g, with some exceeding 1000 mAh / g. In particular, these lithium-rich materials 12 have low reversible capacity, thus their actual lithium replenishment capacity is also high. The actual lithium replenishment capacity is the difference between the delithiation capacity and the reversible capacity, also known as the "irreversible delithiation capacity." For example, the theoretical delithiation capacity of existing Li2NiO2 is 510 mAh / g, and the measured delithiation capacity at 0.1C is 390 mAh / g, but its reversible capacity is approximately 120 mAh / g, resulting in a lithium replenishment capacity of only 270 mAh / g. In contrast, the lithium cobalt oxide catalyst and lithium oxalate cathode lithium replenisher with a mass ratio of 3:1 in this application achieve an actual lithium replenishment capacity of 320 mAh / g at 0.1C.

[0050] In some embodiments of this application, the lithium-rich material 12 is at least one of lithium oxide, lithium peroxide, lithium fluoride, and lithium carbonate. These lithium-rich materials have a high theoretical charge specific capacity, and the positive electrode lithium replenishment agent containing them can actually provide a high lithium replenishment capacity, which helps to better improve the battery capacity.

[0051] In this application embodiment, the mass ratio of lithium-rich material 12 to catalyst 11 can be 1:(0.01-100). In some embodiments, this mass ratio can be 1:(0.1-20). In other embodiments, this mass ratio can be 1:(0.5-20). In still other embodiments, the mass ratio of lithium-rich material 12 to catalyst 11 can be 1:(2-8). Controlling the ratio of lithium-rich material 12 to catalyst 11 within a suitable range can regulate the initial delithiation capacity, actual lithium replenishment capacity, etc. of the positive electrode lithium replenishment agent 100. In some embodiments of this application, the initial delithiation capacity of the positive electrode lithium replenishment agent can be freely varied within the range of 400-1700 mAh / g. In some embodiments, the initial delithiation capacity of the positive electrode lithium replenishment agent can be within the range of 420-1400 mAh / g, and in other embodiments, this value can be adjusted within the range of 420-600 mAh / g. For example, when the lithium-rich material is lithium oxide, the initial delithiation capacity of the positive electrode lithium replenishment agent can be above 400 mAh / g when the mass ratio of lithium oxide to catalyst is greater than or equal to 1:4.

[0052] In this embodiment, the lithium replenishment capacity of the positive electrode lithium replenisher 100 is not less than 400 mAh / g. This high lithium replenishment capacity of the positive electrode lithium replenisher 100 effectively compensates for the irreversible loss of active lithium at the negative electrode during battery manufacturing and cycling, significantly improving the battery's energy density and cycle life. In some embodiments, the lithium replenishment capacity of the positive electrode lithium replenisher 100 can be between 400-1300 mAh / g. In other embodiments, the lithium replenishment capacity of the positive electrode lithium replenisher 100 can be between 400-800 mAh / g.

[0053] The battery term "battery energy density" refers to the amount of electricity stored in a battery per unit weight or volume. Battery energy density is obtained by multiplying the specific capacity of the electrode materials by the discharge voltage; this value is essentially equal to the amount of active lithium divided by the overall volume or mass of the battery. The greater the lithium replenishment capacity provided by the lithium replenishing agent, and the less the mass of residue after replenishment, the greater the improvement in battery energy density.

[0054] In some embodiments of this application, the lithium-rich material 12 is at least one of lithium oxide, lithium peroxide, lithium carbonate, and lithium oxalate. The delithiation products of these lithium-rich materials are oxygen, nitrogen, or CO2 gas, which can be discharged during the venting process of battery manufacturing. At this time, the residual mass of the positive electrode lithium replenishing agent after delithiation is low (i.e., the ratio of the mass of the residue to the mass before delithiation), resulting in minimal increase in battery volume and mass, and is particularly beneficial for improving battery energy density.

[0055] In some embodiments of this application, adding the above-mentioned positive electrode lithium replenisher can increase the energy density of the battery by 0.5%-2% and the cycle life by 30-50%.

[0056] In some embodiments of this application, the intensity ratio of the (003) diffraction peak to the (104) diffraction peak of catalyst 11 can be less than or equal to 1.8, for example, in the range of 1.0-1.8 or 1.4-1.8. The intensity ratio of the (003) diffraction peak to the (104) diffraction peak of oxide-type cathode active materials without lattice reconstruction is usually greater than 2. Compared with oxide-type cathode active materials, the smaller this ratio of catalyst 11, the higher the degree of lattice reconstruction of catalyst 11, the stronger the catalytic activity, and the more active lithium can be generated from lithium-rich materials with low electrochemical activity at a lower delithiation potential.

[0057] In this application, the aforementioned oxide-type positive electrode active material can be undoped or doped. In some embodiments of this application, the aforementioned oxide-type positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, but is not limited thereto. Lithium nickel oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide typically have a layered crystal structure, lithium manganese oxide has a spinel-like structure, and lithium cobalt oxide and lithium nickel manganese oxide can have layered and / or spinel-like structures. The general structural formula of lithium cobalt oxide, lithium manganese oxide, and lithium nickel oxide can be any one of LiMO2, Li2MO2, Li2MO3, Li2MO4, Li3MO4, Li5MO4, and Li6MO4, where M can represent Ni, Co, or Mn.

[0058] In other embodiments of this application, the oxide-type positive electrode active material may further contain doping elements. In this case, the oxide-type positive electrode active material is doped, and the doping element may include at least one of B, P, N, Mg, Al, Ca, Ba, La, Zr, Mo, Nb, Ti, V, Sn, Sb, Cr, Fe, Cu, and Zn. Preferably, lithium nickel cobalt oxide does not contain the doping element Al to avoid overlap with the ternary material lithium nickel cobalt aluminum oxide. Introducing appropriate doping elements can alter at least one of the following: changes in the intrinsic electron orbital overlap, surface properties, and improved structural stability of the oxide-type positive electrode active material.

[0059] In some embodiments of this application, the positive electrode lithium supplement may further include a protective layer 2, which encapsulates the catalyst 11 and the lithium-rich material 12. When the lithium-rich material 12 is at least one of lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate, these lithium-rich materials inherently exhibit high stability in air, thus the presence of the protective layer 2 is permissible, or it may be unnecessary. When the positive electrode lithium supplement does not contain a protective layer 2, the lithium-rich material 2 preferably coats the surface of the catalyst 11. In particular, when the lithium-rich material 12 is lithium oxide and / or lithium peroxide, the presence of the protective layer 2 can enhance the processing performance and structural stability of the positive electrode lithium supplement.

[0060] Specifically, please refer to the following: Figure 2a , Figure 2b and Figure 2c The positive electrode lithium supplement 100 has a core-shell structure, including a core 1 and a protective layer 2 encapsulating the core 1. The core 1 includes a catalyst 11 and a lithium-rich material 12. In the core 10, the lithium-rich material 12 can be coated on the surface of the catalyst 11 (see...). Figure 2a , Figure 2c ), and / or catalyst 11 is dispersed in lithium-rich material 12 (see Figure 2b That is, the structure of the positive electrode lithium supplement 100 may include... Figures 2a-2c At least one of the shown. Wherein, the lithium-rich material 12 can coat the entire surface of the catalyst 11 (see...). Figure 2a Alternatively, only a portion of the surface of catalyst 11 can be coated (see...). Figure 2c ).

[0061] Due to the presence of the protective layer 2, the catalyst 11 and the lithium-rich material 12 are essentially not in contact with air, and their lithium replenishment capacity will not deteriorate due to the absorption of moisture, carbon dioxide, oxygen, etc. from the air, thus further improving the stability of the positive electrode lithium replenishment agent. Furthermore, compared to existing lithium-rich materials such as Li2NiO2 and Li6CoO4, the lithium-rich material 12 here has lower chemical activity and higher structural stability. Moreover, the presence of the protective layer 2 ensures that the lithium-rich material 12 will not directly contact the positive electrode slurry even when it is highly alkaline, resulting in good processing performance of the positive electrode lithium replenishment agent 100. It is compatible with existing lithium-ion battery positive electrode manufacturing processes, does not reduce the fluidity of the positive electrode slurry, and does not affect the coating effect.

[0062] In this embodiment, the protective layer 2 is made of a material with ionic conductivity, so as not to affect the release of active lithium from the subsequent lithium-rich material. Optionally, the constituent material of the protective layer 2 has an ionic conductivity of 10 at room temperature. -8 S·cm -1The above. The material of protective layer 2 may include at least one of lithium fluoride, lithium carbonate, lithium oxalate, lithium acetate, inorganic conductive carbon, organic polymers, and inert oxides. Furthermore, Figure 2a , Figure 2b and Figure 2c In this process, the material of the protective layer 2 is different from that of the lithium-rich material 12. The protective layer 2 has good stability in air, is not easy to absorb water or oxygen, and has low alkalinity. The positive electrode lithium replenishment agent with such a protective layer can have good air stability and processing performance. Moreover, after the positive electrode lithium replenishment agent is delithiated, the residual protective layer (except when it is lithium carbonate) will not increase the risk of gas generation in the battery electrolyte.

[0063] Specifically, for inorganic conductive carbon, examples include amorphous carbon and graphene; for organic polymers, examples include parylene and its derivatives, polymethyl methacrylate (PMMA) and other polyacrylates, polyethylene (PE), polystyrene and other polyolefins; for inert oxides, examples include silicon dioxide, oxides of metals from Group I to Group III (such as aluminum oxide, magnesium oxide, barium oxide, etc.), and non-catalytically active transition metal oxides (such as titanium dioxide, zinc oxide, zirconium oxide, tin oxide, etc.). When the protective layer 2 is inorganic conductive carbon, the conductivity of the positive electrode lithium replenisher can be improved. When the protective layer 2 is lithium carbonate, it can also decompose and generate gas during the delithiation of the positive electrode lithium replenisher, resulting in minimal delithiation residue and further reducing the impact of the positive electrode lithium replenisher on battery mass and volume, thus contributing to improved battery energy density.

[0064] In this application, the thickness of the protective layer 2 can be in the range of 5nm-200nm. In some embodiments of this application, the thickness of the protective layer 2 can be 10nm-100nm. The thickness of the protective layer 2 can be adjusted according to the size of the core. A suitable thickness of the protective layer 2 can ensure that the positive electrode lithium supplement 100 has good processing performance, while avoiding excessive thickness from affecting the timely release of active lithium and increasing battery impedance.

[0065] In some embodiments of this application, the mass of the protective layer 2 can account for 0.01%-10% of the mass of the positive electrode lithium supplement 100. The lower mass percentage ensures that the protective layer has good processing performance of the positive electrode lithium supplement, and even when the protective layer 2 is not lithium carbonate, this lower mass percentage can also result in a lower residual mass of the positive electrode lithium supplement after delithiation.

[0066] In this application, the particle size of the positive electrode lithium supplement 100 can be in the range of 50 nm to 30 μm. In some embodiments of this application, the particle size of the positive electrode lithium supplement 100 can be 300 nm to 15 μm.

[0067] In this embodiment, the particle size of catalyst 11 can be in the range of 10 nm to 25 μm. When the electrochemical activity of lithium-rich material 12 is low (such as lithium oxide, lithium acetate, etc.), catalyst 11 with a smaller particle size is more conducive to the decomposition of lithium-rich material. In some embodiments of this application, the particle size of catalyst 11 can be 10 nm to 20 μm, and more specifically, 20 nm to 200 nm. For example, Figure 2a In the positive electrode lithium replenishment agent shown, the particle size of catalyst 11 can be 100 nm-1 μm; Figure 2b In the illustrated positive electrode lithium replenishment agent, the particle size of catalyst 11 can be 10 nm-2 μm, for example, 10 nm-450 nm. In other embodiments of this application, such as Figure 2c In this process, the particle size of catalyst 11 can be 100nm-25μm, for example, 500nm-15μm.

[0068] Some embodiments of this application (see [see document]) Figure 1 , Figure 2a , Figure 2c A lithium-rich material 12 is coated onto the surface of the catalyst 11 to form a lithium-rich material coating layer of a certain thickness. When the catalyst 11 and the lithium-rich material 12 are in a coating relationship, the catalytic activity of the catalyst 11 can be maximized. The thickness of the lithium-rich material coating layer can be 5 nm-200 nm. Specifically, the thickness can be 10 nm-100 nm or 20 nm-90 nm.

[0069] The positive electrode lithium replenisher 100 provided in this application embodiment has high structural stability and good safety performance. It can efficiently release active lithium under the normal operating voltage of the battery (not exceeding 4.2V), has high lithium replenishment capacity, and its delithiation residue will not increase the risk of electrolyte gas generation or increase cell impedance, which helps to improve the cycle performance and energy density of the battery.

[0070] Accordingly, one embodiment of this application also provides a method for preparing the above-mentioned positive electrode lithium replenishing agent, comprising:

[0071] S01, the oxide-type positive electrode active material is reconstructed to obtain a catalyst; wherein the intensity ratio of the (104) crystal plane diffraction peak to the (003) crystal plane diffraction peak of the catalyst is less than or equal to 2.

[0072] S02, the catalyst is physically fused with a lithium-rich material to obtain a positive electrode lithium replenishing agent; wherein, the catalyst is used to catalyze the decomposition of the lithium-rich material to release active lithium, and the lithium-rich material includes at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate and lithium acetate.

[0073] This preparation method can prepare the following: Figure 1The cathode lithium supplement agent shown in which the catalyst and the lithium-rich material are coated can also be prepared into a cathode lithium supplement agent in which the two are dispersed.

[0074] In step S01 above, the lattice reconstruction method includes one of the following: a) high-energy ball milling of the oxide-type cathode active material; b) high-energy ball milling of the oxide-type cathode active material with a compound of a Group 3 and / or Group 5 element followed by sintering. In this application, after lattice reconstruction of the oxide-type cathode active material, its surface becomes rough, the particle size distribution changes, and the lithium intercalation capacity of the lattice-reconstructed oxide-type cathode active material decreases, its cycle performance deteriorates, and it is more suitable for lithium replenishment.

[0075] In Method a, high-energy ball milling of the oxide-type cathode active material can disrupt its original structure, achieving lattice reconstruction and allowing lithium atoms and transition metal atoms to mix, exposing certain crystal planes and thus exhibiting strong catalytic activity for lithium-rich materials. In Method b, high-energy ball milling and sintering of the lithium-rich catalytic material with compounds of Group III and / or Group V elements can induce recrystallization of the lithium-rich catalytic material, selectively growing in a particular crystal orientation to exhibit catalytic activity. Furthermore, certain Group III and Group V elements can also be incorporated into the crystal structure of the oxide-type cathode active material as dopant elements, improving the structural stability and altering the surface properties of the resulting catalyst.

[0076] In this application embodiment, the rotational speed of the high-energy ball mill is above 350 r / min. In some embodiments, the rotational speed of the high-energy ball mill can be above 400 r / min, for example, 400-1200 r / min or 600-1000 r / min. In some embodiments of this application, the ball-to-material ratio during high-energy ball milling can be in the range of (5-30):1. A higher ball-to-material ratio can better achieve lattice reconstruction. In some embodiments, the ball-to-material ratio during high-energy ball milling can be in the range of (10-30):1.

[0077] In scheme b, the Group 3 elements include at least one of B, Al, Ga, and In, and the Group 5 elements include at least one of N, P, As, Sb, and Bi. The Group 3 and / or Group 5 elements may be added in the form of their oxides, nitrides, chlorides, fluorides, salts, etc. Specifically, the compounds of the Group 3 and / or Group 5 elements may include boron oxide, boron fluoride, boron chloride, boric acid, sodium borohydride; aluminum oxide, aluminum hydroxide, aluminum chloride, aluminum carbonate, aluminum fluoride, aluminum sulfide; gallium fluoride, gallium chloride, gallium oxide; magnesium phosphate, aluminum phosphate, iron phosphate, lithium aluminum titanium phosphate (LATP), etc.

[0078] In some embodiments of this application, in method b, the mass of the compound of a Group 3 and / or Group 5 element can account for 0.05%-10% of the sum of its mass and that of the oxide-type cathode active material. In some embodiments, this mass percentage is 0.5%-2%, which allows the oxide-type cathode active material to undergo better orientation re-growth and improves the lattice reconstruction effect. In method b, the sintering can be carried out in air, and the sintering temperature can be 500-1000°C, for example, 700-800°C. The sintering time can be 5-24 hours, for example, 12-18 hours. Higher sintering temperatures and longer times are more conducive to the recrystallization of the oxide-type cathode active material, resulting in a material with high crystallinity.

[0079] In this application embodiment, the physical fusion method in step S02 can be ball milling, sand milling, or coating, etc. In one embodiment of this application, the physical fusion method can be low-speed ball milling, with a rotation speed lower than that of the high-energy ball milling in step S01. After obtaining the catalyst, the catalyst and lithium-rich material are subjected to low-speed ball milling to avoid damaging the crystal structure of the catalyst formed above. In some embodiments of this application, the rotation speed of the low-speed ball mill is less than or equal to 300 r / min. For example, it can be 200-300 r / min or 200-250 r / min. In some embodiments, the rotation speed of the low-speed ball mill can be below 250 r / min. In some embodiments of this application, the low-speed ball milling is carried out at a low ball-to-material ratio. For example, the ball-to-material ratio during low-speed ball milling can be in the range of (2-10):1. In some embodiments of this application, the diameter of the grinding balls used in the low-speed ball milling is ≤10 mm.

[0080] In other embodiments of this application, Figure 1 The cathode lithium supplement shown can also be prepared by mixing oxide-type cathode active material with lithium-rich material and then performing high-energy ball milling. In this process, lattice reconstruction of the oxide-type cathode active material and coating and / or dispersion of it with the lithium-rich material can be achieved simultaneously.

[0081] In other embodiments of this application, the preparation method further includes: constructing a protective layer encapsulating the catalyst and the lithium-rich material. This is particularly true when the lithium-rich material contains at least one of lithium oxide and lithium peroxide.

[0082] Specifically, the method for constructing the protective layer can include at least one of physical fusion, physical vapor deposition, chemical vapor deposition, coating, thermal decomposition, and in-situ heat treatment. Physical fusion can include ball milling, sand milling, etc., while physical vapor deposition can include vapor deposition, sputtering, etc. The coating method can specifically include one or more combinations of drop coating, brush coating, spray coating, dip coating, blade coating, and spin coating. The coating solution used can directly contain the protective layer material, or it can be a precursor containing the protective layer material, which can subsequently be obtained through co-precipitation or sol-gel methods to obtain the protective layer material.

[0083] In this application, the method for constructing the protective layer can be selected according to the specific material of the protective layer. Among them, physical fusion and coating methods are suitable for constructing protective layers of various materials. Protective layers made of inorganic conductive carbon are particularly suitable for construction by thermal decomposition. Specifically, the organic carbon source and the core material (i.e., the catalyst and the lithium-rich material) can be ground and then subjected to high-temperature heat treatment to thermally decompose the organic carbon source into an inorganic conductive carbon layer. Some organic polymers (such as parylene and its derivatives, such as phenelzine) are more suitable for constructing protective layers with high density and good adhesion by chemical vapor deposition.

[0084] In some embodiments of this application, when the lithium-rich material includes at least one of lithium oxide and lithium peroxide, the protective layer can be constructed using an in-situ heat treatment method, specifically including: placing the core material in dry air or a carbon dioxide stream for in-situ heat treatment. In this way, after in-situ heat treatment, lithium oxide and / or lithium peroxide can form a dense lithium carbonate protective layer in situ. This in-situ heat treatment method is particularly suitable for preparing materials as described above. Figure 2a , Figure 2c The positive electrode lithium supplement is shown. In some embodiments, the temperature of the in-situ heat treatment can be 80-400°C, for example, 100, 120, 150, 180, 200, 220, 250, 300, 320, 350 or 400°C. The time of the in-situ heat treatment can be 0.5-5 hours.

[0085] When a protective layer 2 is present in the positive electrode lithium replenisher, the particle size distribution of the catalyst is wide during lattice reconstruction of the oxide-type positive electrode active material via method a, ranging from nanometers to micrometers. Specifically, the particle size of the catalyst prepared via method a is typically in the range of 10 nm to 20 μm. The final structure of the positive electrode lithium replenisher may simultaneously possess… Figures 2a-2c Three structures. Among them, when the catalyst particle size is large, the resulting cathode lithium supplement agent has the following structure: Figure 2c The main example shown is the catalyst obtained by oriented growth via method b, which has a small and uniform particle size, typically less than 1 μm, for example, in the range of 10 nm to 450 nm. In this case, the structure of the positive electrode lithium supplement prepared by this catalyst is... Figure 2b The image shown is the main one, and there may be a small amount of other images as well. Figure 2a The structure shown.

[0086] Of course, if you want to selectively obtain the above... Figures 2a-2c One of the structures shown can further control the particle size distribution of the catalyst obtained in step S01 before mixing it with the lithium-rich material. Techniques for achieving this particle size distribution include, but are not limited to, cyclone classification, multi-frequency sieving, electrostatic classification, and jet classification. In some embodiments of this application, the particle size distribution of the catalyst can be made to satisfy (D90 particle size - D10 particle size) / D50 particle size < 1.5, to ensure the consistency of lithium replenishment capacity of different batches of cathode lithium replenishing agents.

[0087] The preparation method of the above-mentioned positive electrode lithium replenishing agent provided in the embodiments of this application is simple, efficient and environmentally friendly, and can be mass-produced.

[0088] See Figure 3 This application also provides a battery positive electrode 200, which includes a current collector 10 and a positive electrode material layer 110 sequentially disposed on the current collector 10. The positive electrode material layer 110 includes the aforementioned positive electrode lithium supplement 100 and positive electrode active material 101. The positive electrode material layer 110 may also include a binder 102 and a conductive agent 103.

[0089] In this embodiment, the mass of the positive electrode lithium supplement 100 can be 0.1%-40% of the mass of the positive electrode material layer 110. This mass ratio ensures that the battery made from the positive electrode sheet 200 has a high capacity during the first charge-discharge and multiple subsequent charge-discharge cycles, thereby giving the battery a high energy density and a long cycle life. In some embodiments, this mass ratio is 0.5%-10%.

[0090] In this embodiment, the positive electrode material layer 110 can be formed by coating a positive electrode slurry containing the aforementioned positive electrode lithium supplement 100, positive electrode active material 101, binder 102, and conductive agent 103 onto the current collector 10, followed by drying and pressing. Since the aforementioned positive electrode lithium supplement 100 has a protective layer, it prevents the catalyst, lithium-rich material, and binder in the core material from contacting each other, thus preventing the positive electrode slurry from undergoing a gelling phenomenon. This makes it easier to coat onto the current collector 10, resulting in a film layer with high flatness.

[0091] In this embodiment, the current collector 10 includes, but is not limited to, metal foil or alloy foil. The metal foil includes copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold, or silver foil. The alloy foil includes stainless steel or an alloy containing at least one element selected from copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold, and silver. Optionally, the alloy foil is primarily composed of these elements. The metal foil may further contain doping elements, including but not limited to one or more of platinum, ruthenium, iron, cobalt, gold, copper, zinc, aluminum, magnesium, palladium, rhodium, silver, and tungsten. The current collector 10 may be etched or roughened to form a secondary structure, facilitating effective contact with the positive electrode material layer 110.

[0092] In this application, the positive electrode active material 101 can be at least one of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, nickel cobalt manganese (NCM), and nickel cobalt aluminum (NCA).

[0093] In this application, there are no special restrictions on the binder and conductive agent in the positive electrode material layer 110; conventional materials existing in the art can be used. For example, the binder 102 can be one or more of the following: styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyolefin, sodium carboxymethyl cellulose (CMC), and sodium alginate. For example, the conductive agent 103 can be one or more of the following: conductive carbon black (such as acetylene black, Ketjen black), furnace black, carbon nanotubes, carbon fibers, and graphene.

[0094] This application also provides an electrochemical battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the separator and the electrolyte are located between the positive electrode and the negative electrode, and the positive electrode is the battery positive electrode plate 200 as described above. This electrochemical battery has high energy density and long cycle life.

[0095] This electrochemical battery can be a secondary battery, featuring high cycle performance and high safety. Specifically, this secondary battery can be a lithium secondary battery.

[0096] like Figure 4 As shown, this application embodiment also provides a terminal 300, which can be a mobile phone, tablet computer, laptop, portable computer, smart wearable product or other electronic product. The terminal 300 includes a shell 301 assembled on the outside of the terminal, and a circuit board and battery (not shown in the figure) located inside the shell 301. The battery is the battery provided in the above embodiment of this application. The shell 301 may include a display screen assembled on the front side of the terminal and a back cover assembled on the rear side. The battery can be fixed inside the back cover to supply power to the terminal 300.

[0097] The embodiments of this application will be further described below through multiple examples.

[0098] Example 1

[0099] The preparation of a positive electrode lithium supplement includes:

[0100] Lithium cobalt oxide (LiCoO2) was selected as the catalyst precursor. High-energy ball milling was performed for 48 hours at a ball-to-material ratio of 20:1 and a rotation speed of 350 r / min to achieve lattice reconstruction, yielding the catalyst. Then, the catalyst was mixed with lithium-rich material Li2O at a mass ratio of 4:1 and ball-milled at 200 r / min for 6 hours. The milled powder was then placed in a tube furnace and heated to 400℃, with dry air continuously introduced at a flow rate of 60 sccm for 2 hours to allow some of the Li2O to react and form a lithium carbonate protective layer. After cooling to room temperature, the resulting powder was ground and sieved to obtain the positive electrode lithium supplement.

[0101] The preparation of a pouch cell includes:

[0102] 1) Preparation of battery positive electrode sheet: Single crystal LiCoO2 with a D50 particle size of 14μm was used as the positive electrode active material. The positive electrode active material, the above-mentioned positive electrode lithium supplement, the binder PVDF, and the carbon nanotube (CNT) conductive agent were weighed according to the mass ratio of 94:2:2:2. First, the PVDF was dissolved in NMP solvent, and then the CNTs were added and dispersed evenly. Then, the above-mentioned positive electrode active material and the above-mentioned positive electrode lithium supplement were added at the same time and dispersed evenly to obtain a positive electrode slurry with a viscosity of 3-8 Pa·s and a fineness of less than 25μm. The positive electrode slurry was filtered and coated on an aluminum foil current collector, and then dried, rolled and die-cut to obtain the positive electrode sheet.

[0103] 2) Preparation of negative electrode:

[0104] The silicon-oxygen graphite anode active material (button capacity 500mAh / g, first efficiency 83%) was dispersed in deionized water with conductive carbon black, styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) in a weight ratio of 96.0:1.0:1.5:1.5. The mixture was stirred evenly to obtain anode slurry. The anode slurry was coated on copper foil, dried, compacted and sliced ​​to obtain anode sheet.

[0105] 3) Battery Assembly: Using a 1 mol / L LiPF6 EC+DEC mixture (EC to DEC volume ratio of 1:1) as the electrolyte and a PP / PE / PP three-layer separator as the separator, the positive electrode, separator and negative electrode are stacked in sequence in a glove box and wound into a square bare cell. The bare cell is installed into the battery casing and welded. Then the electrolyte is injected into the battery casing, the battery casing is sealed, and an air bag is reserved to make a soft pack battery with a rated capacity of about 2270mAh for battery performance testing.

[0106] Before conducting electrochemical performance testing on the pouch battery, the battery cell undergoes formation to activate the positive and negative electrode active materials inside the cell and form a stable SEI film on the negative electrode, thereby improving the battery's self-discharge, charge-discharge, and storage performance. During the battery formation stage, gas is generated during film formation within the cell. The positive electrode lithium replenishment agent in Example 1 of this application also generates oxygen gas during delithiation. These gases enter the gas bag. After formation, the gas bag can be cut off, and the cut end can be sealed to obtain the battery ready for shipment. The specific formation process is as follows: After the temperature rises to 80℃, it is charged at a constant current of 0.1C for 12 minutes, then charged at a constant current of 0.5C for 9 minutes, and then charged at 1C for 38 minutes. The voltage limit during the above charging process is 4.48V. Then it is discharged at 1.0C for 3 minutes, with a voltage limit of 3.0V. After that, it is cooled to 45℃, charged at a constant current and constant voltage of 0.2C to 4.48V, with a cutoff current of 0.025C, and then discharged at 0.5C for 60 minutes, with a voltage limit of 3.0V.

[0107] Figure 5 XRD pattern (b) of the catalyst used in Example 1 and XRD pattern (a) of the catalyst precursor are shown. Figure 5 It can be seen that before lattice reconstruction, the intensity ratio of the (003) to (104) diffraction peaks in the XRD pattern of LiCoO2 is greater than 2.2; while after lattice reconstruction, the intensity ratio of the (003) to (104) diffraction peaks in LiCoO2 (i.e., the catalyst) is ≤2. Figure 5 In (a), the ratio is specifically 1.65. It can be seen that the characteristics of the XRD pattern of LiCoO2 changed significantly before and after lattice reconstruction, indicating that it exhibited certain catalytic activity after lattice reconstruction.

[0108] Figure 6 The image shows the XRD pattern of the positive electrode lithium replenishment agent in Example 1. From... Figure 6 It can be seen that it simultaneously exhibits the characteristic peaks of catalyst (LiCoO2), lithium-rich material (Li2O), and protective layer (lithium carbonate), indicating that a composite material containing these three elements—a positive electrode lithium supplement—has been successfully prepared.

[0109] In addition, the positive electrode lithium replenishment agent from Example 1 was assembled into a coin cell on its own, and it was also mixed with lithium cobalt oxide at a ratio of 5%:95% to form a coin cell. Charge-discharge tests were then conducted, and the results were as follows: Figure 7 As shown. Figure 7 The figures (a) show the charge-discharge curves of the positive electrode lithium replenisher in Example 1, and (b) show the charge-discharge curves of the coin cell made by mixing the positive electrode lithium replenisher with lithium cobalt oxide positive electrode active material at a mass ratio of 5%:95%. The process of assembling the positive electrode lithium replenisher into a coin cell using the positive electrode lithium replenisher in Example 1 is as follows: The positive electrode lithium replenisher, acetylene black, and PVDF are weighed in a ratio of 8:1:1, a solvent is added, and a positive electrode slurry is prepared. This slurry is coated onto an aluminum foil current collector, dried, rolled, and cut to obtain a positive electrode sheet. This positive electrode sheet is then combined with a lithium metal sheet, using a 1 mol / L LiPF6 EC+DEC mixture (EC to DEC volume ratio of 1:1) as the electrolyte, and a PP / PE / PP three-layer separator as the separator to form a half cell. A charge-discharge test is performed at a charge-discharge rate of 0.05C, and the test voltage range of the positive electrode sheet is 3-4.5V.

[0110] from Figure 7 As can be seen in (a), the initial delithiation of this positive electrode lithium replenishment agent contributes approximately 500 mAh / g of delithiation capacity, while the reversible capacity (i.e., discharge capacity) is less than 50 mAh / g. Therefore, the lithium replenishment capacity of this positive electrode lithium replenishment agent can be calculated to be above 450 mAh / g. Figure 7 As can be seen in (b), the initial charging capacity of the coin cell battery with the positive electrode lithium supplement + lithium cobalt oxide combination can reach 210 mAh / g, while the charging capacity of the lithium cobalt oxide coin cell battery alone is 180 mAh / g. It can be seen that 5% of the positive electrode lithium supplement provides an additional capacity of about 30 mAh / g to the positive electrode during the first charging process of the battery.

[0111] The residue of the positive electrode lithium replenishing agent in Example 1 of this application after delithiation is a trace amount of LiCoO2 particles, and the particle size of the LiCoO2 particles is distributed between 50nm and 20μm.

[0112] Example 2

[0113] The preparation of a positive electrode lithium supplement includes:

[0114] Commercially available lithium cobalt oxide powder with a particle size in the range of 2-50 μm was selected as the catalyst precursor. Boron oxide powder and lithium aluminum titanium phosphate (LATP) powder were added to it to obtain a mixed powder. The mass percentage of both boron oxide powder and LATP powder in the mixed powder was 1%. The mixed powder was placed in a ball mill jar and ball-milled for 12 hours at a ball-to-material ratio of 15:1 and a rotation speed of 380 r / min. The mixed powder was then transferred to a tube furnace and sintered at 700 °C for 8 hours in an air atmosphere. After grinding and sieving, lithium cobalt oxide with lattice reconstruction was obtained, i.e., the catalyst, with a particle size of 10 nm-2 μm and an intensity ratio of (003) crystal plane diffraction peak to (104) crystal plane diffraction peak of 1.55.

[0115] The above catalyst was mixed with lithium-rich material Li2O at a mass ratio of 3:1 and ball-milled at 250 r / min for 3 hours. The ball-milled mixture was then removed, ground, and sieved to obtain the core material. Nano-γ-Al2O3 powder with a D50 particle size of 30 nm (mass percentage of 0.2%) was added to the core material and ball-milled at a ball-to-material ratio of 2:1 and a speed of 150 r / min for 2 hours. After further grinding and sieving, the positive electrode lithium replenishing agent was obtained.

[0116] The positive electrode lithium replenishing agent in Example 2 includes, for example: Figure 2b The structure described herein includes a protective layer with a thickness of 20 nm, and a core comprising lithium oxide and a catalyst dispersed in the lithium oxide. The catalyst is flattened and has a D50 particle size of approximately 200 nm.

[0117] Following the method described in Example 1, the positive electrode lithium replenishment agent of Example 2 was used to make a soft-pack battery with a rated capacity of about 2270mAh.

[0118] Example 3

[0119] The preparation of a positive electrode lithium supplement includes: selecting lithium cobalt oxide (LiCoO2) material with a particle size in the range of 5-20 μm (D50 particle size of 14 μm) as a catalyst precursor, and performing high-energy ball milling for 14 h at a ball-to-material ratio of 10:1 and a rotation speed of 400 r / min to achieve lattice reconstruction to obtain a catalyst; mixing the catalyst with lithium oxalate (Li2C2O4) at a mass ratio of 3:1, and performing low-speed ball milling for 8 h at a ball-to-material ratio of 8:1 and a rotation speed of 200 r / min; and grinding and sieving the resulting powder to obtain the positive electrode lithium supplement.

[0120] The positive electrode lithium replenishment agent structure in Example 3 can be as follows: Figure 1As shown, the catalyst (lattice-reconstructed lithium cobalt oxide) and a lithium-rich coating layer of Li2C2O4 encapsulating the catalyst are included. The intensity ratio of the (003) to (104) diffraction peaks of the catalyst is 1.7, the thickness of the Li2C2O4 layer is about 0.5 μm, the particle size of the lithium supplement is 5.5 μm-25 μm, and the D50 particle size is about 15 μm.

[0121] Following the method described in Example 1, the positive electrode lithium replenishment agent of Example 3 was used to make a soft-pack battery with a rated capacity of about 2270mAh.

[0122] Example 4

[0123] The preparation of a positive electrode lithium supplement includes: selecting lithium cobalt oxide (LiCoO2) material with a particle size in the range of 5-20 μm (D50 particle size of 14 μm) as a catalyst precursor, mixing it with lithium-rich material LiF at a mass ratio of 1:1, and ball milling it at a ball-to-material ratio of 20:1 and a rotation speed of 350 r / min for 48 h; then grinding and sieving the resulting powder to obtain the positive electrode lithium supplement. The positive electrode lithium supplement includes a catalyst (lattice-reconstructed lithium cobalt oxide) and a lithium-rich coating layer LiF encapsulating the catalyst. The intensity ratio of the (003) to (104) diffraction peaks of the catalyst is 1.45, the thickness of the LiF layer is about 2 μm, and the particle size D50 of the lithium supplement is about 18 μm.

[0124] Following the method described in Example 1, the positive electrode lithium replenishment agent of Example 4 was used to make a soft-pack battery with a rated capacity of about 2270mAh.

[0125] Example 5

[0126] The preparation of a positive electrode lithium supplement includes: selecting NCM811 single crystal material (D50 particle size of 14μm) with a particle size in the range of 5-30μm as a catalyst precursor, and performing high-energy ball milling for 48h at a ball-to-material ratio of 30:1 and a rotation speed of 400r / min to achieve lattice reconstruction to obtain a catalyst; then mixing the catalyst with lithium-rich material Li2O at a mass ratio of 4:1, and performing ordinary ball milling at a rotation speed of 250r / min for 3 hours; then placing the ball-milled mixed powder in a tube furnace, continuously introducing dry CH4 gas, then evacuating the furnace tube and repeating the process 3 times to purge the air from the furnace tube, controlling the flow rate of CH4 gas at 10mL / min, raising the furnace temperature to 900℃ and maintaining it for 4 hours to complete the graphitized carbon coating; after the furnace temperature cools down to room temperature, removing the powder, grinding and sieving the obtained powder to obtain the positive electrode lithium supplement.

[0127] The positive electrode lithium replenisher in Example 5 includes, as follows: Figure 2a , Figure 2cIn the described structure, the D50 particle size of the core NCM811 is 14 μm, the thickness of the lithium oxide coating layer formed on the surface of the NCM811 is 1.5 μm, and the thickness of the graphitized carbon protective layer is 20 nm. The residue of the positive electrode lithium replenishment agent after delithiation in Example 5 consists of NCM811 particles and graphitized carbon.

[0128] Referring to the methods of Examples 1-5 above, positive electrode lithium replenishing agents of other examples were prepared according to the parameters listed in Table 2, and comparative materials with catalysts that were not lattice remodeled under the same conditions were provided. According to the coin cell preparation method described in Example 1, the lithium replenishing agents of each example and the corresponding comparative lithium replenishing agents were prepared into coin cells, and charge-discharge tests were conducted at a rate of 0.05C within a voltage range of 3-4.5V. The charge-discharge curves of each coin cell were tested, and the specific capacity (i.e., delithiation specific capacity) of each lithium replenishing agent was calculated. The results are shown in Table 2.

[0129] Table 2 Structural parameters and charging capacity of each lithium replenisher

[0130]

[0131] As can be seen from the test results in Table 2, when the catalyst is not reconstructed by the crystal lattice, it basically has no ability to catalyze lithium-rich materials, resulting in extremely low charge capacity of the obtained composite material and basically no ability to replenish lithium.

[0132] To further highlight the beneficial effects of the embodiments of this application, according to the method for preparing a soft-pack full battery in Example 1, the positive electrode lithium supplementer of the above embodiments was mixed with the positive electrode active material - lithium cobalt oxide at a mass ratio of 2%:98% to prepare a soft-pack battery. The electrochemical performance was tested at a constant temperature of 25°C and a charge-discharge rate of 0.7C, as shown in Table 3, with a test voltage range of 3-4.48V (vs. Li / Li+). In addition, this application also provides the performance test results of a lithium cobalt oxide battery with the existing positive electrode lithium supplementer Li2NiO2 added under the same conditions (Comparative Example 1) and a lithium cobalt oxide full battery without the positive electrode lithium supplementer of the embodiments of this application added (Comparative Example 2).

[0133] Table 3 Performance test results of each battery

[0134]

[0135] As shown in Table 3, the introduction of the cathode lithium supplement in this application embodiment significantly improves the battery's cycle performance and also enhances its energy density and initial coulombic efficiency to some extent. Furthermore, when the mass ratio of the cathode lithium supplement in this application embodiment to the existing Li2NiO2 lithium supplement is the same as that of the existing Li2NiO2 lithium supplement, the latter demonstrates superior performance in improving battery energy density, initial coulombic efficiency, and cycle life compared to the former.

Claims

1. A positive electrode lithium replenishing agent, characterized in that, The positive electrode lithium replenishment agent includes a catalyst and a lithium-rich material; the catalyst is an oxide-type positive electrode active material after lattice reconstruction, and the intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak of the catalyst is less than or equal to 2. The catalyst can catalyze the lithium-rich material to decompose at a voltage below 4.2V to release active lithium. The lithium-rich material is selected from at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate and lithium acetate. The mass ratio of the lithium-rich material to the catalyst is 1:(0.5-100).

2. The positive electrode lithium replenishing agent as described in claim 1, characterized in that, The intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak of the catalyst is 1.0-1.

8.

3. The positive electrode lithium replenishing agent as described in claim 1, characterized in that, The lattice-reconstructed oxide-type positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt aluminum oxide.

4. The positive electrode lithium replenishing agent as described in claim 3, characterized in that, The oxide-type positive electrode active material after lattice reconstruction also contains doping elements, including at least one of B, P, N, Mg, Al, Ca, Ba, La, Zr, Mo, Nb, Ti, V, Sn, Sb, Cr, Fe, Cu and Zn.

5. The positive electrode lithium replenishing agent as described in claim 1, characterized in that, The catalyst has a particle size of 10 nm to 25 μm.

6. The positive electrode lithium replenishing agent as described in claim 1, characterized in that, The surface of the catalyst is coated with the lithium-rich material, and / or the catalyst is dispersed in the lithium-rich material.

7. The positive electrode lithium replenishing agent as described in claim 6, characterized in that, The lithium-rich material forms a lithium-rich material coating layer with a thickness of 10nm-20μm on the surface of the catalyst.

8. The positive electrode lithium replenishing agent according to any one of claims 1-7, characterized in that, The positive electrode lithium replenishing agent also includes a protective layer that encapsulates the catalyst and the lithium-rich material, the protective layer having ionic conductivity.

9. The positive electrode lithium replenishing agent as described in claim 8, characterized in that, The protective layer is made of at least one of lithium fluoride, lithium carbonate, lithium oxalate, lithium acetate, lithium phosphate, inorganic conductive carbon, organic polymers, and inert oxides.

10. The positive electrode lithium replenishing agent as described in claim 8, characterized in that, The thickness of the protective layer is 5nm-200nm.

11. The positive electrode lithium replenishing agent as described in claim 8, characterized in that, The mass of the protective layer is 0.01%-10% of the mass of the positive electrode lithium supplement.

12. The positive electrode lithium replenishing agent according to any one of claims 1-7, characterized in that, The particle size of the positive electrode lithium replenishing agent is 50nm-30μm.

13. A method for preparing a positive electrode lithium replenishing agent, characterized in that, The preparation method includes: A catalyst is obtained by lattice reconstruction of an oxide-type positive electrode active material; wherein the lattice reconstruction method includes one of the following: a) high-energy ball milling of the oxide-type positive electrode active material so that the intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak is less than or equal to 2; b) high-energy ball milling of the oxide-type positive electrode active material with a compound of a group III and / or group V element and then sintering to obtain an oxide-type positive electrode active material with lattice reconstruction, wherein the intensity ratio of the (003) crystal plane diffraction peak to the (104) crystal plane diffraction peak is less than or equal to 2; The catalyst is physically fused with a lithium-rich material to obtain a positive electrode lithium replenisher; wherein the catalyst can catalyze the decomposition of the lithium-rich material at a voltage below 4.2V to release active lithium, and the lithium-rich material is selected from at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate and lithium acetate; the mass ratio of the lithium-rich material to the catalyst is 1:(0.5-100).

14. A battery positive electrode sheet, characterized in that, The positive electrode sheet of the battery includes a current collector and a positive electrode material layer disposed on the current collector. The positive electrode material layer includes a positive electrode lithium supplement as described in any one of claims 1-12 or a positive electrode lithium supplement prepared by the preparation method described in claim 13, as well as a positive electrode active material, a binder, and a conductive agent.

15. The battery positive electrode sheet as described in claim 14, characterized in that, The mass of the positive electrode lithium supplement is 0.1%-40% of the mass of the positive electrode material layer.

16. An electrochemical battery, characterized in that, It includes a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the positive electrode is the battery positive electrode sheet according to any one of claims 14-15.

17. A terminal, characterized in that, The device includes a housing, a motherboard and a battery located inside the housing, the battery including the electrochemical battery as described in claim 16, the electrochemical battery being used to power the terminal.

Citation Information

Patent Citations

  • Lithium supplementing slurry for lithium ion energy storage device, and preparation method and application of lithium supplementing slurry

    CN110838573A